2017
DOI: 10.1007/s10549-017-4358-6
|View full text |Cite|
|
Sign up to set email alerts
|

Reducing chemotherapy use in clinically high-risk, genomically low-risk pN0 and pN1 early breast cancer patients: five-year data from the prospective, randomised phase 3 West German Study Group (WSG) PlanB trial

Abstract: The excellent five-year outcomes in clinically high-risk, genomically low-risk (RS ≤ 11) pN0-1 patients without adjuvant chemotherapy support using RS with standardised pathology for treatment decisions in HR+ HER2-negative EBC. Ki-67 has the potential to support patient selection for genomic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
165
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(174 citation statements)
references
References 33 publications
3
165
0
6
Order By: Relevance
“…Patients should be assessed periodically to confirm the absence of tumor progression. Patients with Stage 1 or limited Stage 2 disease (including those with N1 nodal involvement), and those with low-intermediate grade tumors, lobular BCs, low-risk genomic assays (especially the recurrence score, which may be sent from a core biopsy [26]), or "luminal A" signatures, do not benefit substantially from neoadjuvant or adjuvant chemotherapy [27,28]. These patients may receive endocrine therapy alone.…”
Section: Invasive Bc-early Stagementioning
confidence: 99%
“…Patients should be assessed periodically to confirm the absence of tumor progression. Patients with Stage 1 or limited Stage 2 disease (including those with N1 nodal involvement), and those with low-intermediate grade tumors, lobular BCs, low-risk genomic assays (especially the recurrence score, which may be sent from a core biopsy [26]), or "luminal A" signatures, do not benefit substantially from neoadjuvant or adjuvant chemotherapy [27,28]. These patients may receive endocrine therapy alone.…”
Section: Invasive Bc-early Stagementioning
confidence: 99%
“…The trial is ongoing to accrue patients with intermediate risk (RS 11-25), and we await the next interim analysis to be published. PlanB, a trial using the RS as a key tool in decision-making for chemotherapy, has already demonstrated disease-free survival rates of 94% in women with RS between 11 and 25, treated with hormone therapy alone [17]. …”
Section: Discussionmentioning
confidence: 99%
“…The authors emphasized on the one hand that patients with a low RS had a very good prognosis with purely endocrine therapy, and on the other that the substantial discordance between traditional pathological parameters and the RS makes further standardization necessary and that wellstandardized and validated gene expression tests ought to be taken into account in the choice of treatment. In another recent analysis from the PlanB study, Nitz et al also investigated clinical and pathological prognostic factors such as nodal status, grading, tumor size, Ki-67, PR, and four immunohistochemical markers (IHC4) alongside the recurrence score [21]. The prognostic significance of the RS was particularly marked with tumors that had moderate Ki-67 values (> 10 %, < 40 %).…”
Section: Comparison Of Different Multigene Testsmentioning
confidence: 99%